Development of a Biology E-module Based on Guided Discovery Learning on Ecosystem and Environmental Topics to Improve High School Student Learning Outcomes - Dimas Mahendra Wijaya; Ida Bagus Putu Arnyana; Desak Made Citrawathi (Universitas Pendidikan Ganesha, 2022)
This study aims to develop a product in the form of an e-module of biology learning based on guided discovery learning that is valid, practical, and effective. This research is part of development research, with a development research design that adapts the ADDIE development model. The stages of the ADDIE development model include (1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The validation test phase involves material experts and teacher practitioners, media experts, and linguists. The practicality test phase involves teacher practitioners and students. The activity test phase involved 36 students from class X IPA 1. The results of development research are (1) the developed e-module obtained valid criteria based on content and construct validity; (2) the product developed has practical criteria based on the teacher and student response questionnaires; (3) e-module biology learning based on guided discovery learning effective used to improve student learning outcomes, this is evidenced by obtaining a significance value of 0.0001 (p < 0.05) and classical learning completeness of 94% with very good criteria.